Rural-Urban Migration and Translocal Livelihoods in West Africa: Review of Literature (African Human Mobility Review, 2025)
In this paper we review literature examining migration and translocal livelihoods across the West African subregion. Translocal livelihood is defined as the networks of interlinkages and interdependence that exist between mobile and non-mobile populations in the region. The paper focuses on translocal livelihoods between rural and urban populations. It adopted a non-systematic literature review approach. The literature indicates that rural-urban migration across West Africa has created various degrees of interdependence between migrants and their household members in the places of origin. Translocal networks diminishes the dichotomies between urban and rural spaces. During translocal relations, the movement of resources between migrants and their household members living in the places of origin is bidirectional. Moreover, translocal ties are sustained by the extended family system. However, there is limited understanding about how translocality leads to the sustenance of origin society cultural values such as language, beliefs, and family system among migrants and their children.